Effects of gender, age, season on the mineral profiles of impala on the Experimental Farm in Messina (Aepyceros melampus) (Lichtenstein, 1812) - Webb, E.C. (Edward Cottington) (University of Pretoria, 2015)
Dissertation (MScAgric)--University of Pretoria, 2014.